Clinical manifestation, Haemato-biochemical evaluation and Therapeutic management in dog suffering from Jaundice associated with babesiosis - Kumar, Vipan; Pal, Satinder; *, Amandeep; Pal, Heigo; Kumar, Parveen; Wadhawan, V.M (IJRDO - JOURNAL OF BIOLOGICAL SCIENCE, 2016)
A bitch was presented to Veterinary Polyclinic, Jalandhar with history of Jaundice.Hematological and biochemical examination revealed Hyperbilirubinemia and babesiosis. Thebitch was treated with berenil at the dose rate of 3.5mg per kilogram body weight and supportivetherapy to tone up general metabolism and restoration of normal liver function. After one weekof treatment bitch was negative for heamoprotozoa and recovered fully after three week.